Physico-chemical properties of water, proximate composition, minerals and antioxidant of six species of seagrasses at Merambong shoal, Johore, Malaysia - Wan Nawi, Wan Hazma (2017)
Seagrass has not yet been claimed as a dietary stuff and source of medicine for human consumption. Since several seagrass species are edible, investigation of nutrient, proximate composition and antioxidant properties in marine macrophytes are very important. Thus, the objectives of this study were to assess the physico-chemical and nutrient status of seawater in the seagrass habitat, determine the proximate composition, mineral contents and screening the antioxidant properties of six seagrass species; Enhalus acoroides, Thalassia hemprichii, Cymodocea serrulata, Halodule uninervis, Halophila ovalis (small and big-leaved) and Halophila spinulosa at Merambong shoal, Johore during the low tide, from March to August 2013. Nutritive proximate compositions were estimated following analysis methods described by the Association of Official Analytical Chemists. Results showed that seagrasses were high in carbohydrate (48.99-83.03%), fiber (10.02-27.48%) and ash (11.46-41.69%), and low in lipid content (0.02-1.22%). The protein content showed variation with species ranged 5.50% to 16.04%. The moisture content range from 6.68-21.49%. Macro-(Nitrogen-N, Phosphorus-P, Potassium-K, Calcium-Ca, Magnesium-Mg) and micro-(Zinc-Zn, Iron-Fe, Manganese-Mn, Copper-Cu) minerals measured using Atomic Absorption Spectrophotometer (AAS) and their concentrations varied with species and time. Minerals content; N, P, K, Ca, Mg, Zn, Fe, Mn, and Cu ranged 3308.00-36826.67 mg kg-1, 429.33-3400.00 mg kg-1, 2025.33-29520.00 mg kg-1, 4680.00-25280.00 mg kg-1, 3244.00-13040.00 mg kg-1, 85.33-180.00 mg kg-1, 922.67-5657.33 mg kg-1, 13.33-129.33 mg kg-1 and 3.20-29.20 mg kg-1 respectively. Trend in micro-nutrient contents categorically followed a simple pattern, Fe>Zn>Mn>Cu. Methanol extracts of seagrasses were used to examine antioxidant activity by DPPH radical scavenging activity, total phenolic content (TPC) content and total flavonoid content (TFC). DPPH scavenging activity, TPC and TFC significantly different (p<0.05) between seagrass species with month. Rhizomes of E. acoroides and H. uninervis had relatively higher antioxidant activity (0.34 mg ml-1 in June and 0.26 mg ml-1 in July and August of EC50 value respectively). Total phenolic content of seagrasses at Merambong shoal ranged 1.02 to 91.77 mg GAE kg-1 with lower content in March and higher in August. The values of TFC were also varied among species and months (ranged from 43.25 to 361.46 mg QE kg-1). Based on biplots generated by Principle component analysis (PCA), there were clear separation of proximate composition and mineral contents of seagrass species with locations from Malaysia and other regions. In conclusion, seagrasses possessed essential nutrient content and good antioxidant properties that could be utilized for pharmaceutical and nutraceutical uses.